(untitled) (Biological Sciences - PJSIR, 1997)
Chloropyranodioxins (I) prepared by the reaction of malonyl chloride with mixed ketone were converted into 7- (phenylamino)-pyranodioxins (II) which underwent the phenoxide rearrangement to yield the corresponding pyridinodioxins (III), whose structures were determined by chemical conversions and spectroscopic studies.